IMPLEMENTASI AKAD WADI’AH PADA TABUNGAN SANTRI DI PONDOK PESANTREN AL-ITTIHAD CIANJUR (Studi Kasus Di Altie Bank) - Dudang Abdul Karim; Wahyudin; Mohamad Aldy Al Attar (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
This research aims to analyze the implementation of wadi’ah yad amanah contract in the management of santri savings at Pondok Pesantren Al-Ittihad Cianjur. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation study, and analyzed interactively following the Miles and Huberman model: data reduction, data display, and conclusion drawing/verification. The findings reveal that the implementation of wadi’ah yad amanah in santri savings has been carried out well and systematically, adhering to sharia principles, ensuring the security of deposited funds, and fostering trust among santri. Internal support from the pesantren management and the trust of santri parents contribute to the sustainability of the program, while the main challenges involve understanding of the akad among santri and technical administration. The research concludes that the practice of wadi’ah yad amanah in santri savings is effective in promoting the values of trustworthiness, honesty, and financial discipline within the pesantren environment.